Deprescribing cholinesterase inhibitors and memantine in dementia: guideline summary. Issue 4 (16th February 2019) - Reeve, Emily; Farrell, Barbara; Thompson, Wade; Herrmann, Nathan; Sketris, Ingrid; Magin, Parker J; Chenoweth, Lynn; Gorman, Mary; Quirke, Lyntara; Bethune, Graeme; Hilmer, Sarah N
Abstract: Introduction: Cholinesterase inhibitors (ChEIs) and memantine are medications used to treat the symptoms of specific types of dementia. Their benefits and harms can change over time, particularly during long term use. Therefore, appropriate use of ChEIs and memantine involves both prescribing these medications to individuals who are likely to benefit, and deprescribing (withdrawing) them from individuals when the risks outweigh the benefits. We recently developed an evidence‐based clinical practice guideline for deprescribing ChEIs and memantine, using robust international guideline development processes. Main recommendations: Our recommendations aim to assist clinicians to: identify individuals who may be suitable for a trial of deprescribing ChEIs and memantine (such as those who do not have an appropriate indication, those who have never experienced a benefit, those who appear to be no longer benefitting, and those who have severe or end‐stage dementia); and taper treatment and monitor individuals during the deprescribing process. Changes in management as a result of the guideline: Deprescribing ChEIs and memantine through shared decision making with individuals and their caregivers by: ▶ determining their treatment goals; ▶ discussing benefits and harms of continuing and ceasing medication, from the start of therapy and throughout; and ▶ engaging them in monitoring after discontinuation, while informing carers that the individual will continue to decline after discontinuation. This approach may reduce adverse drug reactions and medication burden, leading to improved quality of life in people with dementia.